Overview of qualitative risk assessments for the introduction and spread of HPAI H5N1 Virus - Métras, Raphaëlle; Costard, Solenne (International Food Policy Research Institute, 2009)
From 2006 to the present, 11 countries in Africa reported outbreaks of highly pathogenic avian influenza (HPAI) H5N1: Egypt, Sudan, Djibouti, Niger, Nigeria, Burkina Faso, Côte d’Ivoire, Ghana, Togo, Benin, and Cameroon. Other than Egypt, where the disease is endemic, the last cases of HPAI H5N1 in Africa reported to the World Organization for Animal Health (OIE) occurred in Nigeria (June and July 2008) and Togo (September 2008). In Indonesia, the disease has become endemic since its introduction in 2004. Qualitative risk assessment is the most common type of assessment to guide routine decisionmaking, especially in data-scarce environments. It allows for the development of risk mitigation strategies and for the identification of data gaps, and provides useful recommendations for future research. A joint research team from the Royal Veterinary College (RVC) in London and International Livestock Research institute (ILRI) in Nairobi led five qualitative risk assessments in Ghana, Ethiopia, Kenya, Nigeria and Indonesia between October 2008 and June 2009. The work was carried out by national collaborators: Paa Kobina Turkson (Ghana), Bewket Siraw and Hassen Chaka (Ethiopia), Dennis Onkundi (Kenya), Garba Maina Ahmed (Nigeria), and Syafrison Idris and Maria F. Palupi (Indonesia). In each of the five countries, a stakeholders workshop was held in October or November 2008. These workshops had three main objectives: to present the risk assessment objectives to the stakeholders; to define the risk questions of interest for each country; and to outline the risk pathways. Drawing on the workshop outcomes, the risk assessments (RAs) were then conducted from January to April 2009. Given the scarcity of data in these environments, input data for the models were collected by expert opinion elicitation, with key informants responding to questionnaires. The RA reports are currently being finalized.